2014
DOI: 10.1016/j.otsr.2014.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of progressive tibial lengthening in dogs using the Ilizarov technique. Comparison with and without associated intramedullary K-wires

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
0
11
1
4
Order By: Relevance
“…Assuming that the methods of fixation used in osteosynthesis must resists the main mechanical forces at the site of fracture, the tie-in configuration has great biomechanical advantage, as it resists to all these forces even though it requires fewer implants than conventional ESF (Beck & Simpson 1999, Popkov et al 2014.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Assuming that the methods of fixation used in osteosynthesis must resists the main mechanical forces at the site of fracture, the tie-in configuration has great biomechanical advantage, as it resists to all these forces even though it requires fewer implants than conventional ESF (Beck & Simpson 1999, Popkov et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, McCartney (2007) reported the removal of the apparatus between six and eight weeks in animals younger than 1 year, and eight to ten weeks in animals over one year old. Popkov et al (2014) combined Ilizarov ESF and intramedullary pins in dogs aged 1 to 5 years with experimental fractures and closed growth plates and observed that all fractures were completely consolidated by 28 days post-operatively. Egger et al (1993) observed that conventional ESF destabilization (dynamization) after four weeks post-operative enabled the formation of periosteal callus in dogs due to an increase in the mechanical force at the site of fracture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Авторы отмечают как сокращение дли-тельности внешней фиксации, так и снижение количе-ства осложнений, обусловленных продолжительным периодом нахождения аппарата внешней фиксации на конечности. Важно отличать комбинированную методику удлинения, когда внешний остеосинтез и интрамедуллярное армирование выполняются одно-временно, обеспечивая механические и биологические преимущества данной методики [14,18,21], от удли-нения с последующим армированием в момент снятия аппарата внешней фиксации (lengthening then rodding), когда интрамедуллярный остеосинтез является лишь внутренним тутором уже удлиненной кости с целью профилактики переломов и деформаций [31].…”
Section: вопросы детской ортопедииunclassified
“…Другим спосо-бом, стимулирующим костное сращение при удлинении конечностей, является интрамедуллярное эластичное армирование, в том числе, с биоактивным покрытием [16][17][18][19][20]. Экспериментальные исследования показали, что интрамедуллярное введение эластичных стержней не нарушает целостности питательной артерии и, таким образом, не противоречит принципам метода Илизарова [14,21]. Наконец, биоактивное кальций-фосфатное или гидроксиапатитное покрытие способно стимулировать костное сращение, препятствует миграции имплантов и уже находит свое применение при лечении деформаций у детей с метаболическими остеопатиями [16,17].…”
unclassified